Analyzing What Drives Consumers to Buy: An SEM–PLS Study at Onde-Onde Bo Liem Empunala Mojokerto - Prastika, Alifah Septa; Rendra Erdkhadifa; Mubarak, Reza (Mabny: Journal of Sharia Management and Business, 2025)
This study is based on the efforts that need to be made by a business in maintaining its existence amidst business competition with similar products and services offered to the market. This condition requires business actors to identify and understand current market needs. Therefore, an entrepreneur needs to study consumer behavior patterns. Based on this, efforts are needed to organize strategies so that the business owned can develop, one of which is by analyzing factors that can contribute to consumer purchasing decisions for goods or services. This study applies quantitative methods and associative research types with a sampling technique, namely quota sampling where the number of samples is 100 respondents. The data analysis technique used is Structural Equation Modeling - Partial Least Square. Referring to the results of the analysis carried out, it shows that in the Onde-onde Bo Empunala business, the factors that contribute significantly to the purchasing decision process are the quality of the products owned and brand image, while the service and location factors do not contribute significantly.